Psychometric properties of Bahasa Version of The Household Emergency Preparedness Scale (HEPS) - Calisanie, Nyayu Nina Putri (Holistic Nursing Plus, 2025)
Background: The Household Emergency Preparedness Scale (HEPS) is designed to measure preparedness levels within households. Despite its effectiveness in English-speaking populations, culturally adapted versions for non-English speakers remain limited, especially in Southeast Asia. Translating HEPS into Bahasa Indonesia could offer a relevant tool for Indonesian communities frequently affected by natural disasters. Objective: This study aimed to translate and validate the Bahasa Indonesia version of HEPS. Methods: This study involved a three-phase process, including translation, cultural adaptation, and psychometric validation. Forward and backward translations were conducted, followed by expert panel reviews and content validity was evaluated through Aiken’s V coefficient, with ratings from five experts. A confirmatory factor analysis (CFA) to assess construct validity. Reliability was measured using Cronbach’s alpha and the Intraclass Correlation Coefficient (ICC). Results: The Bahasa Indonesia HEPS demonstrated strong content validity, with most items achieving an Aiken’s V score of 1.00. The CFA showed acceptable model fit across all subscales, with fit indices within recommended ranges (CFI > 0.90, RMSEA < 0.08). Reliability was high, with Cronbach’s alpha exceeding 0.80 for all subscales except one, which exhibited moderate inter-rater reliability (ICC = 0.546–0.732). Conclusion: The Bahasa Indonesia HEPS is a reliable and valid tool for assessing household emergency preparedness in Indonesia. It holds promise for both community-level assessments and policy planning in disaster-prone areas, providing a culturally relevant measure to enhance emergency preparedness initiatives.